1995
DOI: 10.2337/diab.44.8.992
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Glutathione Depletion and Oxidative Stress in Early Embryogenesis in Glucose-Induced Rat Embryo Culture

Abstract: Recent studies have demonstrated the protective effects of supplementing free oxygen radical scavenging enzymes against hyperglycemia-induced embryonic malformations. In this study, the glutathione (GSH)-dependent protection system in hyperglycemia-induced embryopathy was investigated. Rat embryos at the early head-fold stage (day 9.5) cultured in 66.7 mmol/l glucose for 48 h showed significant growth retardation and an increase in the frequency of malformations. The concentration of GSH and activity of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 0 publications
1
77
0
Order By: Relevance
“…It has been suggested that embryonic dysmorphogenesis in a diabetic or hyperglycaemic environment might be induced by the generation of ROS [9] and that ROS-scavenging enzymes can protect diabetic embryos from glucoseinduced malformations [10]. Trocino et al showed that anomalies induced in rat embryos grown under hyperglycaemic conditions are associated with glutathione (GSH) depletion and that GSH esters can attenuate hyperglycaemia-induced abnormalities [11]. The teratogenic effect of diabetic serum was prevented by superoxide dismutase (SOD) and N-acetylcysteine in rat whole embryo culture [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that embryonic dysmorphogenesis in a diabetic or hyperglycaemic environment might be induced by the generation of ROS [9] and that ROS-scavenging enzymes can protect diabetic embryos from glucoseinduced malformations [10]. Trocino et al showed that anomalies induced in rat embryos grown under hyperglycaemic conditions are associated with glutathione (GSH) depletion and that GSH esters can attenuate hyperglycaemia-induced abnormalities [11]. The teratogenic effect of diabetic serum was prevented by superoxide dismutase (SOD) and N-acetylcysteine in rat whole embryo culture [12].…”
Section: Introductionmentioning
confidence: 99%
“…mutase, can prevent structural defects caused by high glucose in rodent embryos [13,14,17,18,19,20,21,22,23], this indicates that hyperglycaemia-induced oxidative stress plays a causal role in diabetes-induced congenital defects.…”
mentioning
confidence: 95%
“…Since excess glucose increases ROS in embryos [13,14,15], and oxidants can regulate cellular signalling pathways, including those that control transcriptional responses [30,31], excess oxidants could interfere with signals that induce the expression of Pax-3. Here we tested this hypothesis by alleviating oxidative stress with antioxidant administration, and by inducing oxidative stress with an electron transport complex III inhibitor.…”
mentioning
confidence: 99%
“…This may illustrate a difference in acute and chronic effects on the embryonic tissue exerted by a diabetic environment, but could also indicate that the major effect of the diabetic milieu is a decrease in antioxidant capacity rather than an outright increase in oxygen radical production. This notion is strengthened by the clear antiteratogenic effect of supplementing either NAC (present study) or GSH ester [41] to high-glucose cultured embryos. In addition, it has been shown that culture of rat embryos in high glucose concentration decreases cellular glutathione levels and decreases the activity of the rate-limiting GSH-synthesising enzyme, g -glutamylcysteine synthetase [41].…”
Section: Discussionmentioning
confidence: 73%
“…This notion is strengthened by the clear antiteratogenic effect of supplementing either NAC (present study) or GSH ester [41] to high-glucose cultured embryos. In addition, it has been shown that culture of rat embryos in high glucose concentration decreases cellular glutathione levels and decreases the activity of the rate-limiting GSH-synthesising enzyme, g -glutamylcysteine synthetase [41].…”
Section: Discussionmentioning
confidence: 73%